Mechanical properties and effects of alginate on proliferation and cardiac differentiation of mouse embryonic stem cells. - Sneha Oberai. (2013)
Embryonic stem cells (ESCs) can proliferate indefinitely and have the ability to differentiate into specific lineages, while maintaining an unaltered genome. They have a huge potential to improve the field of medicine with applications in cell based therapy and drug toxicity studies. However successful delivery of ESCs into the body remains a problem due to low cell availability and immuno-rejection by the body. While many hydrogels have been established for the purpose of safe ESC encapsulation and delivery, they must also be able to control the pluripotency and differentiation of these cells. Alginate hydrogel is currently being studied for cell encapsulation due to its simple linear chain structure and biocompatibility. The mechanical properties of this alginate hydrogel affect the proliferation and differentiation of ESCs and can be modified to either maintain ESCs in a pluripotent state or to channel them into specific lineage differentiation. This research project studies various alginate concentrations and the effect their resulting mechanical properties have on the proliferation and cardiac differentiation of encapsulated E14TG2a mouse ESCs (mESCs). Six different alginate bead concentrations - 0.5%, 0.7%, 1.0%, 1.1%, 1.3% and 1.5% - were studied in Static cell culture conditions and some were also studied in HARV reactor conditions. Analytical tests such as Light